Implementation of Balance Exercise to Prevent the Risk of Falls in the Elderly at Nursing Home Damai Ranomuut Manado - Ningrum, Puspita; Sondakh, Fangli; Rondonuwu, Junytha (Universitas Bondowoso, 2024)
ABSTRACT Background: The decline in functional ability in the elderly, which begins with the weakening of body cells, the function of the immune system becomes weaker, resulting in increased risk factors for falls. The risk of falling is a condition that is at risk of physical damage or health problems. The risk of falling can be done with balance exercises to identify and reduce the risk of falling due to changes in physical or psychological conditions. Method: Objectives Obtain a picture of Balance Exercise in Preventing the Risk of Falls in the Elderly. This research method is a case study with a descriptive type of research, the subjects of the case study are 2 elderly people who are at risk of falling Result: after three days of implementation can be concluded that subject I and subject II experienced increased balance and decreased risk of falling Conclusion: Balance Exercise can help prevent the risk of falls in the elderly. Suggestions Balance Exercise needs to be taught to the person in charge of the nursing home so that it can be applied to the elderly who are at risk of falling in the nursing home.